An integrated design approach for small grid-tied permanent magnet wind generators - Khan, M. A.; Zorlu, S.; Guan, R.; Pillay, P.; Visser, K. D. (IEEE, 2007)
This paper presents a design approach for a permanent magnet (PM) wind generator, intended for grid-tied wind energy system applications. The generator is directly coupled to a wind turbine and its AC output is rectified, then boosted to a suitable DC voltage level and finally inverted to AC for connection to a grid. This paper presents an integrated design approach for these grid-tied PM wind generators. The approach incorporates sizing and design procedures for a wind turbine and a PM wind generator in the context of the system topology within which they will operate. The wind generator is sized and its design optimized for the desired output voltage and power at the grid Furthermore, all the inefficiencies of the components between the generator and turbine are included in the sizing and optimization processes. A sizing and design procedure for the turbine is included in the design process.
Keywords: TURBINES; Energy & Fuels; Engineering